Brucella ceti and Brucellosis in Cetaceans - Moreno, Edgardo; Guzmán-Verri, Caterina; Gonzalez-Barrios, Rocio; Hernandez, Gabriela; Morales, Juan A.; Barquero-Calvo, Elias; Chaves-Olarte, Esteban (Frontiers in Cellular and Infection Microbiology, 2012)
Since the first case of brucellosis detected in a dolphin aborted fetus, an increasing number of Brucella ceti isolates has been reported in members of the two suborders of cetaceans: Mysticeti and Odontoceti. Serological surveys have shown that cetacean brucellosis may be distributed worldwide in the oceans. Although all B. ceti isolates have been included within the same species, three different groups have been recognized according to their preferred host, bacteriological properties, and distinct genetic traits: B. ceti dolphin type, B. ceti porpoise type, and B. ceti human type. It seems that B. ceti porpoise type is more closely related to B. ceti human isolates and B. pinnipedialis group, while B. ceti dolphin type seems ancestral to them. Based on comparative phylogenetic analysis, it is feasible that the B. ceti ancestor radiated in a terrestrial artiodactyl host close to the Raoellidae family about 58 million years ago. The more likely mode of transmission of B. ceti seems to be through sexual intercourse, maternal feeding, aborted fetuses, placental tissues, vertical transmission from mother to the fetus or through fish or helminth reservoirs. The B. ceti dolphin and porpoise types seem to display variable virulence in land animal models and low infectivity for humans. However, brucellosis in some dolphins and porpoises has been demonstrated to be a severe chronic disease, displaying significant clinical and pathological signs related to abortions, male infertility, neurobrucellosis, cardiopathies, bone and skin lesions, strandings, and death.